2021
DOI: 10.5455/aim.2021.29.15-20
|View full text |Cite
|
Sign up to set email alerts
|

Simulation in Clinical Nursing Education

Abstract: Background: Simulation constitutes a teaching method and a strategy for learning and understanding theoretical knowledge and skills in the nursing and medical field. Objective: To review and present modern data related to this issue. Methods: Literature review of data related to the issue derived from Medline, Cinhal, and Scopus databases, in English, using the following keywords: nursing, simulation, simulator, nursing laboratory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 46 publications
2
41
0
5
Order By: Relevance
“…We mentioned that a different spectrum of associations could arise, and a sense of security after gaining experience can be evoked in individual performances. Koukourikos et al (2021) also confirm that students who use simulation teaching opportunities are less likely to be uncertain in problematic situations in clinical practice. They should be able to take the lead and manage a team of experts as experienced professionals.…”
Section: ) Benefits To Studentssupporting
confidence: 60%
“…We mentioned that a different spectrum of associations could arise, and a sense of security after gaining experience can be evoked in individual performances. Koukourikos et al (2021) also confirm that students who use simulation teaching opportunities are less likely to be uncertain in problematic situations in clinical practice. They should be able to take the lead and manage a team of experts as experienced professionals.…”
Section: ) Benefits To Studentssupporting
confidence: 60%
“…En Latinoamérica y en Chile, en los últimos años, existe un crecimiento exponencial de la simulación clínica que ha fortalecido el aprendizaje de las habilidades procedimentales de los estudiantes de Enfermería 19,[32][33] . Sin embargo, no todas las escuelas de Enfermería presentan la infraestructura, la planificación y la integración que poseen los grandes centros de simulación de países como Estados Unidos, Canadá y el Reino Unido, por los altos costos económicos que esto implica 19,[32][33] . En consecuencia, el entrenamiento en los simuladores es mucho menor, lo que se traduce en que los estudiantes afianzan sus habilidades psicomotrices en la práctica clínica real.…”
Section: Simulación Clínica En Enfermeríaunclassified
“…La realidad de Latinoamérica y de Chile, aún no es comparable con la de los países más avanzados. Si bien hay recintos educacionales que tienen cursos basados en simulación, no es la mayoría, por lo tanto, la práctica en los ambientes clínicos sigue siendo importante en el aprendizaje de las habilidades procedimentales, a pesar del dilema ético que conlleva esta situación [32][33] . Este escenario se torna más crítico aún en el año 2020, donde se declara la pandemia por COVID-19.…”
Section: Desafíos Futuros De La Simulación Clínicaunclassified
“…The gap between theory and practice is thus significantly reduced. It was concluded that further development of simulation, in conjunction with other instructional techniques, can significantly aid students' efforts to become integrated and successful health care professionals (Koukourikos et al 2021).…”
Section: Practice Implication For Simulation In Nursing Educationmentioning
confidence: 99%